If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -1x = 7 + x Solving 13 + -1x = 7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 13 + -1x + -1x = 7 + x + -1x Combine like terms: -1x + -1x = -2x 13 + -2x = 7 + x + -1x Combine like terms: x + -1x = 0 13 + -2x = 7 + 0 13 + -2x = 7 Add '-13' to each side of the equation. 13 + -13 + -2x = 7 + -13 Combine like terms: 13 + -13 = 0 0 + -2x = 7 + -13 -2x = 7 + -13 Combine like terms: 7 + -13 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| 30x^2-11x-1=0 | | 64-4x=16 | | 6x-2=1+x | | (x+1)(x-1)(x-3)= | | 5(3x-2)-(x-3)=4(4x+5)+13 | | p/14=-12 | | 2x^2+6x-8=-8 | | r+5-1=3r+8 | | t/-1.2=3.8 | | 7/3-4/-848 | | 2x+3=5x+3-x | | 1/3(3)(8) | | x-19=-35 | | 6r-5-5=14 | | -5=8-1x | | 4(3y-5)=2(7y+3) | | 5(3a-2)=25 | | V=bmjforB | | 9/8.5/8 | | 1.5/3p=4.5 | | -57=-3(1-6m)+6(5m+7) | | 17-4x=-19 | | 98x5/8 | | 2x+8=2(x-8) | | X^2-2x+y^2+4y-21=0 | | 7/10x9/10 | | 12*6+3(18-10)+5*3-11=x-10*5 | | 8/3+10y=3y-4 | | 10-.5x=-1.5x | | 1.2u+.625=-.8u+1.25 | | -3(7x+7)+4(2x+2)=-65 | | 1x+1+7=180 |